2018
DOI: 10.3389/fneur.2018.00334
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Brain Structural Network in Parkinson’s Disease With and Without Rapid Eye Movement Sleep Behavior Disorder

Abstract: Background and objectiveRapid eye movement sleep behavior disorder (RBD) has a strong association with alpha synucleinpathies such as Parkinson’s disease (PD) and PD patients with RBD tend to have a poorer prognosis. However, we still know little about the pathogenesis of RBD in PD. Therefore, we aim to detect the alterations of structural correlation network (SCN) in PD patients with and without RBD.Materials and methodsA total of 191 PD patients, including 51 patients with possible RBD (pRBD) and 140 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 66 publications
7
20
0
Order By: Relevance
“…However, this study finds that the PDD with fall group had significantly less GMV in the left calcarine and right inferior frontal gyrus than that of the PDD without fall group. This finding is similar to a study comparing the brain structures of PD patients with and without rapid eye movement sleep behavior disorder [ 40 ]. Furthermore, the association between sleep disorders and falls in PD patients has been reported in a separate case-control study [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, this study finds that the PDD with fall group had significantly less GMV in the left calcarine and right inferior frontal gyrus than that of the PDD without fall group. This finding is similar to a study comparing the brain structures of PD patients with and without rapid eye movement sleep behavior disorder [ 40 ]. Furthermore, the association between sleep disorders and falls in PD patients has been reported in a separate case-control study [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…This was consistent with previous studies (11,17,25,26). That is to say, the information of brain can be integrated effectively in both PD patients and NC.…”
Section: Small-world Properties and Global Measure Of Pd And Ncsupporting
confidence: 93%
“…It receives information from "homeostatic afferent" sensory pathways through the thalamus and sends output to some other limbic-related structures, such as the amygdala and ventral striatum (39). A study focused on structural correlation network reported that the nodal betweenness and degree of limbic system was increased (11). And a PET study of iRBD reported increased metabolism in hippocampus.…”
Section: Increased Efficiency Of Bilateral Thalamus (Pd-prbd Vs Pd-nmentioning
confidence: 99%
See 1 more Smart Citation
“…Resilience indicates the tolerance of the network against random or targeted attack, and is relevant to the stability of the network ( Achard et al, 2006 ; He et al, 2008 ). Various neurological diseases are characterized by the topological properties of the brain structural covariance network ( Yao et al, 2010 ; Shi et al, 2012 ; Tao et al, 2018 ; Zou et al, 2018 ; Liu et al, 2019 ), such as the small-world property, network centrality, and resilience ( He et al, 2008 , 2009 ).…”
Section: Introductionmentioning
confidence: 99%